Societal burden of stroke rehabilitation: Costs and health outcomes after admission to stroke rehabilitation - Winke van Meijeren-Pont; Sietske J. Tamminga; Paulien H. Goossens; Iris F. Groeneveld; Henk Arwert; Jorit J.L. Meesters; Radha Rambaran Mishre; Thea P.M. Vlieland; Wilbert B. van den Hout (Medical Journals Sweden, 2021)
Objective: To estimate societal costs and changes in health-related quality of life in stroke patients, up to one year after start of medical specialist rehabilitation. Design: Observational. Patients: Consecutive patients who received medical specialist rehabilitation in the Stroke Cohort Outcomes of REhabilitation (SCORE) study. Methods: Participants completed questionnaires on health-related quality of life (EuroQol EQ-5D-3L), absenteeism, out-of-pocket costs and healthcare use at start and end of rehabilitation and 6 and 12 months after start. Clinical characteristics and rehabilitation costs were extracted from the medical and financial records, respectively. Results: From 2014 to 2016 a total of 313 stroke patients completed the study. Mean age was 59 (standard deviation (SD) 12) years, 185 (59%) were male, and 244 (78%) inpatients. Mean costs for inpatient and outpatient rehabilitation were US$70,601 and US$27,473, respectively. For inpatients, utility (an expression of quality of life) increased significantly between baseline and 6 months (EQ-5D-3L 0.66-0.73, p = 0.01; visual analogue scale 0.77-0.82, p < 0.001) and between baseline and 12 months (visual analogue scale 0.77-0.81, p < 0.001). Conclusion: One-year societal costs from after the start of rehabilitation in stroke patients were considerable. Future research should also include costs prior to rehabilitation. For inpatients, health-related quality of life, expressed in terms of utility, improved significantly over time.